Impact of postoperative necrotizing enterocolitis after neonatal cardiac surgery on neurodevelopmental outcome at 1 year of age - Knirsch, Walter; De Silvestro, Alexandra; Rathke, Verena; L’Ebraly, Christelle; Natterer, Julia C.; Schneider, Juliane; Sekarski, Nicole; Latal, Beatrice; Borradori-Tolsa, Cristina; Bouhabib, Maya S.; Fuhrer Kradolfer, Katharina; Glöckler, Martin; et al. (Frontiers in Pediatrics, 2024)
What is the impact of postoperative cardiogenic necrotizing enterocolitis (NEC) on neurodevelopmental (ND) outcome at one year of age? Key findings:Postoperative NEC is associated with a prolonged intensive care unit (ICU) length of stay (LOS) and the total duration of the hospitalization, constituting an additional risk factor for neurodevelopmental impairment in newborns with congenital heart disease.Postoperative NEC constitutes an additional risk of neurodevelopmental impairment in infants undergoing cardiac surgery and should be prevented with clinical alert strategies and management.